2015
DOI: 10.15171/ijhpm.2015.23
|View full text |Cite
|
Sign up to set email alerts
|

Measuring access to urban health services using Geographical Information System (GIS): a case study of health service management in Bandar Abbas, Iran

Abstract: Background: The current distribution of and access to health services along with the future health needs of the population have prompted wide application of Geographic Information Systems (GISs). During recent years, GIS has been used in public health management for planning and organization of healthcare services. This study investigates geographical accessibility of residential areas in Bandar Abbas, Iran to healthcare services. Methods: Accessibility was evaluated by using Floating Catchment Area (FCA), min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 19 publications
1
14
1
1
Order By: Relevance
“…One important parameter in measuring the spatial accessibility is the drive distance between the supply and demand (hospital and home) locations [ 30 ]. Using a travel-time threshold (d) of 5 min in the 2SFCA calculation, an acceptable spatial distance to hospitals in Iran’s metropolitan areas has been estimated at 1–1.5 km travel-distance (0.621–0.932 mile) or at 5–10 min travel-time [ 40 ]. The estimated 5 min travel-time buffer for each neighbourhood’s centroid and hospitals service area zones was derived from the ArcMap Network Analyst tool.…”
Section: Methodsmentioning
confidence: 99%
“…One important parameter in measuring the spatial accessibility is the drive distance between the supply and demand (hospital and home) locations [ 30 ]. Using a travel-time threshold (d) of 5 min in the 2SFCA calculation, an acceptable spatial distance to hospitals in Iran’s metropolitan areas has been estimated at 1–1.5 km travel-distance (0.621–0.932 mile) or at 5–10 min travel-time [ 40 ]. The estimated 5 min travel-time buffer for each neighbourhood’s centroid and hospitals service area zones was derived from the ArcMap Network Analyst tool.…”
Section: Methodsmentioning
confidence: 99%
“…With regard to demographics, it is expected that variations may affect target CA and also surrounding areas. Notably, recent efforts have been made to integrate accessibility and location–allocation models in geographic information systems, thus considering spatial planning ( 19 , 20 ). Outcomes not necessarily related to HF access may include a better understanding of the level of performance of healthcare on the basis of the sustained HF costs.…”
Section: Discussionmentioning
confidence: 99%
“…There are a few studies with the application of GIS in public health. For example, studies on the analysis of access to treatment centers [74][75][76]. There are also studies examining the impact of distance [77], developing a map for planning prevention of the diseases [27,34] There is no doubt some studies using GIS can be applied in substance abuse research as shown by studies by [82][83] in which applying GIS in their studies towards drug users to inform of the formation and optimization of public health intervention, hence providing a greater understanding of at risk drug user populations.…”
Section: Integration Of Gis and Multivariate Analysis In Substance Abmentioning
confidence: 99%